Environment permissible concentrations of glyphosate in drinking water can influence the fate of neural stem cells from the subventricular zone of the postnatal mouse - Masood, Muhammad Irfan; Naseem, Mahrukh; Warda, Salam A.; Tapia-Laliena, María Angeles; Rehman, Habib ur; Nasim, Muhammad Jawad; Schäfer, Karl Herbert (Environmental pollution, 2021)
The developing nervous system is highly vulnerable to environmental toxicants especially pesticides. Glyphosate pesticide induces neurotoxicity both in humans and rodents, but so far only when exposed to higher concentrations. A few studies, however, have also reported the risk of general toxicity of glyphosate at concentrations comparable to allowable limits set up by environmental protection authorities. In vitro data regarding glyphosate neurotoxicity at concentrations comparable to maximum permissible concentrations in drinking water is lacking. In the present study, we established an in vitro assay based upon neural stem cells (NSCs) from the subventricular zone of the postnatal mouse to decipher the effects of two maximum permissible concentrations of glyphosate in drinking water on the basic neurogenesis processes. Our results demonstrated that maximum permissible concentrations of glyphosate recognized by environmental protection authorities significantly reduced the cell migration and differentiation of NSCs as demonstrated by the downregulation of the expression levels of the neuronal ß-tubulin III and the astrocytic S100B genes. The expression of the cytoprotective gene CYP1A1 was downregulated whilst the expression of oxidative stresses indicator gene SOD1 was upregulated. The concentration comparable to non-toxic human plasma concentration significantly induced cytotoxicity and activated Ca2+ signalling in the differentiated culture. Our findings demonstrated that the permissible concentrations of glyphosate in drinking water recognized by environmental protection authorities are capable of inducing neurotoxicity in the developing nervous system.